Polycarbonate composition and preparation method thereof

By introducing polysiloxane and phosphorus-containing bisphenol copolymer into the polycarbonate material, the problem of insufficient flame retardant and impact resistance of polycarbonate materials is solved, and high impact resistance is achieved Halogen flame retardant properties, good compatibility and environmental friendliness.

CN119410119AActive Publication Date: 2025-02-11WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202411774845.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-11
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The flame retardant properties of existing polycarbonate materials are poor, especially at low temperatures, which limits their application range.

Method used

By introducing polysiloxane and phosphorus-containing bisphenol copolymer into the polycarbonate substrate, the phosphorus-silica copolycarbonate is formed, which improves its flame retardant and impact resistance.

Benefits of technology

It has achieved high impact, halogen-free flame retardant properties of polycarbonate materials, with good compatibility and environmental friendliness, and has broadened its application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410119A_ABST
    Figure CN119410119A_ABST
Patent Text Reader

Abstract

The invention relates to a polycarbonate composition and a preparation method thereof, and the polycarbonate composition mainly comprises the following components in parts by weight: 65-85 parts of aromatic polycarbonate, 15-35 parts of phosphorus-silicon copolycarbonate, 0.05-1 part of an antioxidant and 0.1-1 part of a lubricant. According to the polycarbonate composition prepared by the invention, the double-screw extruder is adopted for blending, the compatibility of the phosphorus-silicon copolycarbonate and the aromatic polycarbonate is good, the flame retardant property of the polycarbonate composite material is greatly improved through the phosphorus-silicon synergistic flame retardant effect, and the use of a halogen-free flame retardant is avoided; the reduction of the mechanical property of the polycarbonate material caused by the small-molecule flame retardant is improved, and the low-temperature impact resistance of the material is greatly improved by the siloxane chain segment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polycarbonate composition and a preparation method thereof, in particular to a high-impact halogen-free flame-retardant polycarbonate composition and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) is a high molecular polymer containing carbonate bonds in the molecular chain, which can be divided into aliphatic, alicyclic, aliphatic-aromatic and aromatic polycarbonates. Aromatic polycarbonate has excellent mechanical properties, heat resistance, impact toughness, electrical insulation and light transmittance, low creep resistance and water absorption, good dimensional stability, and excellent dielectric properties. It can be used as a thermoplastic engineering plastic and is widely used in automobiles, electronic equipment, construction, office supplies, optical disks, sports equipment, medical care, computers, aerospace and other fields. However, the unmodified polycarbonate material has poor flame retardancy and low impact resistance at low temperatures, which limits the application range of polycarbonate. Therefore, in order to expand its application range, it needs to be modified.

[0003] At present, the main modification method is to add flame retardants to the polycarbonate matrix. Common flame retardants for polycarbonate include halogen, phosphorus, silicon, sulfonate, etc. Halogen flame retardants will seriously affect the light transmittance and impact strength of PC. Sulfonate flame retardants have good flame retardant effects and have little effect on the light transmittance of polycarbonate, but sulfonates contain sulfur, which will cause harm to the environment and human body. Phosphorus flame retardants are cheap, have good flame retardant effects, and are halogen-free and environmentally friendly, but phosphorus flame retardants have poor heat resistance and excessive addition will directly affect the light transmittance of polycarbonate. Silicone flame retardants have the characteristics of high efficiency, non-toxicity, low smoke, and drip resistance, and have little effect on light transmittance, processing performance, and mechanical properties, but their high price limits their use in industry. Therefore, according to the current research situation, adding a single flame retardant cannot simultaneously meet the performance requirements of polycarbonate.

[0004] Chinese patent CN115124707A discloses a phosphorus-silicon copolymer polycarbonate and its preparation method and application. DOPO reacts with polysiloxane to introduce the phosphorus-containing monomer into the side chain of polysiloxane, and then introduces it into the polycarbonate molecular chain by chemical copolymerization. The compatibility of the prepared copolycarbonate with aromatic polycarbonate needs to be further improved. Patent CN 202110098391.5 discloses an intrinsic flame retardant copolymer PC and its preparation method. Bisphenol S and siloxane chain segments are introduced into conventional PC molecular chains to improve the intrinsic flame retardant properties of PC. Its flame retardant energy level reaches UL94V0 (3mm) at the highest, but the impact performance of the material is poor; U.S. Patent US20070129492 introduces siloxane monomers into the PC molecular chain to prepare flame-retardant PC materials with low smoke release and low heat release. The intrinsic flame retardant performance reaches V0 (3mm), which needs to be further improved; CN 105849171 B discloses a method for preparing low-smoke and low-heat release train interior components. Branched PC end-capped with cyanophenol, tetrabromobisphenol A copolymer PC, and siloxane PC are synthesized at the polymerization end, and they are blended with conventional PC and additives such as flame retardants in a certain proportion. Blending will cause flame retardant precipitation and affect the mechanical properties of the material.

[0005] In summary, it is necessary to develop a high-impact halogen-free flame-retardant polycarbonate material that has good compatibility with polycarbonate and is environmentally friendly, which can make up for the shortcomings of polycarbonate to a certain extent and broaden the application field of polycarbonate materials. Summary of the invention

[0006] The object of the present invention is to provide a polycarbonate composition and a preparation method thereof, and to improve the flame retardant and impact resistance of the polycarbonate by introducing a polysiloxane and a phosphorus-containing bisphenol copolymer into a polycarbonate substrate.

[0007] The purpose of the present invention can be achieved by the following technical means:

[0008] A polycarbonate composition comprising the following components (by weight):

[0009] (1) 65 to 85 parts by weight of an aromatic polycarbonate;

[0010] (2) 15 to 35 parts by weight of phosphorus-silicon copolycarbonate containing structural units of formula 1 and formula 2,

[0011]

[0012]

[0013] In Formula 2, the p is selected from an integer of 20 to 90, preferably 30 to 50;

[0014] (3) 0.05 to 1 parts by weight of an antioxidant;

[0015] (4) 0.1 to 1 parts by weight of a lubricant.

[0016] Preferably, the composition of the present invention comprises:

[0017] (1) 65 to 80 parts by weight of aromatic polycarbonate

[0018] (2) 20 to 35 parts by weight of phosphorus-silicon copolycarbonate containing structural units of formula 1 and formula 2

[0019] (3) 0.2 to 0.4 parts by weight of an antioxidant

[0020] (4) 0.25 to 0.6 parts by weight of a lubricant.

[0021] More preferably, the composition of the present invention comprises:

[0022] (1) 70 to 80 parts by weight of aromatic polycarbonate

[0023] (2) 20 to 30 parts by weight of phosphorus-silicon copolycarbonate containing structural units of formula 1 and formula 2

[0024] (3) 0.25 to 0.35 parts by weight of an antioxidant

[0025] (4) 0.25 to 0.35 parts by weight of a lubricant.

[0026] Wherein, the aromatic polycarbonate is bisphenol A type polycarbonate with a weight average molecular weight of 20,000-40,000, preferably bisphenol A type polycarbonate with a weight average molecular weight of 22,000-35,000.

[0027] The polycarbonate composition is characterized in that the phosphorus silicon copolycarbonate containing structural units of formula 1 and formula 2 has a weight fraction of the structural unit represented by formula 1 of 75 to 95%, preferably 80 to 90%, and a weight fraction of the structural unit represented by formula 2 of 5 to 25%, preferably 10 to 20%.

[0028] The phosphorus-silicon copolycarbonate is obtained by polymerizing the phosphorus-containing bisphenol shown in Formula 3 and the phosphorus-containing polysiloxane monomer shown in Formula 4 with phosgene.

[0029]

[0030] In Formula 4, the p is selected from integers of 20 to 90, preferably 30 to 50.

[0031] The weight average molecular weight of the phosphorus silicon copolycarbonate is 20000-30000 g / mol, preferably 25000-30000 g / mol.

[0032] The phosphorus silicon copolycarbonate containing the structural units of formula 1 and formula 2 is prepared by the following method, which comprises the following steps:

[0033] (1) preparing an aqueous phase: mixing the phosphorus-containing bisphenol shown in Formula 3, a capping agent, an alkali metal hydroxide, and water, and after the solid is completely dissolved, adding a catalyst to form an aqueous phase;

[0034] (2) preparing a comonomer solution: mixing liquid phosgene with an inert organic solvent in a mixer to prepare a phosgene solution, and at the same time, mixing the phosphorus-containing polyoxyalkylene monomer represented by Formula 4 with an inert organic solvent in another mixer to prepare a comonomer solution;

[0035] (3) Polymerization reaction: adding the prepared phosgene solution and comonomer solution dropwise to the aqueous phase to carry out polymerization reaction, and maintaining the temperature of the reaction system at 30-35° C. for 2-4 hours to obtain a novel phosphorus-silicon copolycarbonate emulsion;

[0036] (4) post-treatment: purifying the novel phosphorus-silicon copolycarbonate emulsion prepared in step (3) and removing the organic solvent to obtain the product;

[0037] In step (1), the end-capping agent is selected from one or more of phenol, p-tert-butylphenol, p-cumylphenol, and p-cyanophenol, preferably p-tert-butylphenol;

[0038] In step (1), the alkali metal hydroxide is selected from one or more of potassium hydroxide, sodium hydroxide, lithium hydroxide, and cesium hydroxide, preferably sodium hydroxide;

[0039] The molar ratio of the phosphorus-containing bisphenol: capping agent: alkali metal hydroxide: water is selected from 1: (0.01-0.03): (2.0-3.0): (25-50), preferably 1: (0.012-0.027): (2.2-3.0): (30-50);

[0040] The catalyst is triethylamine, tetrabutylammonium bromide, tetrabutylammonium chloride, preferably tetrabutylammonium bromide; the molar ratio of the catalyst to the phosphorus-containing bisphenol is 0.0001-0.006:1, preferably 0.0001-0.005:1;

[0041] In step (2), the inert organic solvent is selected from one or more of dichloromethane, chloroform, dichloroethane, and trichloroethane, preferably dichloromethane; the weight ratio of phosgene to the inert organic solvent is 1:(5-40), preferably 1:(10-30); the weight ratio of the comonomer to the inert organic solvent is selected from 1:(3-6), preferably 1:(4-5);

[0042] The phosphorus-containing bisphenol shown in Formula 3 used in the present invention is obtained by reacting o-diallyl bisphenol A with DOPO. DOPO, o-diallyl bisphenol A, ethanol, and a certain concentration of sodium hydroxide solution are added to a reactor, and the mixture is reacted for a period of time at a certain stirring rate and temperature. The solvent is removed by rotary evaporation to obtain a phosphorus-containing bisphenol monomer. The molar ratio of DOPO to o-diallyl bisphenol A is 1:1 to 20:1; the molar ratio of o-diallyl bisphenol A to ethanol is 1:10 to 1:40; the concentration of the sodium hydroxide solution is 10 to 40%; the molar ratio of o-diallyl bisphenol A to sodium hydroxide is 1:0.001 to 1:0.1; the stirring rate is 200 to 1000 rpm, the reaction temperature is 50 to 160°C, and the reaction time is 2 to 10 hours. The reaction equation is shown in Formula 5.

[0043]

[0044] The polysiloxane comonomer shown in formula 4 is obtained by reacting a polysiloxane containing an allylphenol end group with DOPO. Specifically, DOPO, a polysiloxane containing an allylphenol end group, ethanol, and a sodium hydroxide solution are added to a reactor, reacted at a certain stirring rate and temperature, and the solvent is removed by rotary evaporation to obtain a phosphorus-containing bisphenol monomer; the molar ratio of DOPO to the polysiloxane containing an allylphenol end group is 1:1 to 20:1; the molar ratio of the polysiloxane containing an allylphenol end group to ethanol is 1:10 to 1:40; the concentration of the sodium hydroxide solution is 10 to 40%; the molar ratio of the polysiloxane containing an allylphenol end group to sodium hydroxide is 1:0.001 to 1:0.1; the stirring rate is 200 to 1000 rpm, the reaction temperature is 50 to 160°C, and the reaction time is 2 to 10 hours; the reaction equation is shown in formula 6.

[0045]

[0046] In the step (3), the molar ratio of the added phosgene to the comonomer is (1.1-1.4):1, preferably (1.1-1.3):1;

[0047] The pH of the reaction system during the polymerization reaction is 11 to 12, preferably 11.5 to 11.7; the polymerization reaction is preferably carried out under stirring, and the stirring rate is 500 to 800 rpm, preferably 600 to 800 rpm.

[0048] In step (4), the post-treatment can be carried out by conventional methods in the art, for example: the copolymer emulsion is first separated into oil and water, and the oil phase is sequentially washed with alkali, acid and water, and the solvent is removed from the oil phase after washing, and the phosphorus silicon copolycarbonate is obtained after crushing and drying.

[0049] The antioxidant is any one of hindered phenols, organophosphorus, thioesters, and hindered amines, or a combination of two or more thereof; preferably, one or more of Ciba's antioxidant series 1076, 1010, 168, 421S, and 627 are used.

[0050] The lubricant is any one of pentaerythritol stearate (PETS), modified ethylene bis stearamide (modified EBS), and silicone powder, or a combination of two or more thereof.

[0051] On the other hand, the present invention also provides a method for preparing the high-impact halogen-free flame-retardant polycarbonate composition, which comprises putting 65 to 85 parts by weight of aromatic polycarbonate, 15 to 35 parts by weight of phosphorus silicon copolycarbonate, 0.05 to 1 part by weight of antioxidant, and 0.1 to 1 part by weight of lubricant into a high-speed mixer for mixing and stirring, and then putting the mixture into a twin-screw extruder for extrusion.

[0052] Preferably, the preparation method of the high-impact halogen-free flame-retardant polycarbonate composition described above comprises putting 65 to 85 parts by weight of aromatic polycarbonate, 15 to 35 parts by weight of phosphorus silicon copolycarbonate, 0.05 to 1 part by weight of antioxidant, and 0.1 to 1 part by weight of lubricant into a high-speed mixer for mixing and stirring, adding the mixture into a twin-screw extruder, controlling the temperature of the conveying section of the twin-screw extruder to 210-220°C, the temperature of the plasticizing section to 225-245°C, the temperature of the metering section to 225-240°C, controlling the screw speed to 200-600rpm, controlling the vacuum degree of the vacuum device of the twin-screw metering section to be less than -0.7 bar, pulling strips, water cooling, air drying, pelletizing, and drying to obtain the product.

[0053] The positive effects of the present invention are:

[0054] The phosphorus-silicon copolycarbonate in the polycarbonate composition of the present invention has good compatibility with the polycarbonate material. The flame retardant performance of the polycarbonate material is greatly improved through the synergistic flame retardant effect of phosphorus-silicon. It has the characteristics of halogen-free and environmentally friendly. Compared with small molecule flame retardants, it avoids the reduction of the mechanical properties of the polycarbonate caused by the addition of flame retardants and the problem of small molecule migration. In addition, the phosphorus-silicon copolycarbonate added in the present invention, the polysiloxane chain segment forms a large-sized silicon domain in the material, which can greatly improve the impact resistance of the polycarbonate material.

[0055] The composition of the present invention has the following properties:

[0056] The impact strength (J / m) at room temperature is greater than 650, the impact strength (J / m) at -40℃ is greater than 550, and the flame retardant performance of the 1.5mm sample is V0 (UL94). BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1NMR spectrum of BPA-P

[0058] Figure 2 P-PDMS-55 NMR spectrum DETAILED DESCRIPTION

[0059] In order to better understand the technical solution of the present invention, the content of the present invention is further described below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0060] The analysis and evaluation methods involved in the embodiments or comparative examples are as follows:

[0061] (1) The molecular weight was tested by gel permeation chromatography (GPC) using a Waters 1515 gel permeation chromatograph, with tetrahydrofuran as the solvent, PS as the standard sample, temperature at 30°C, and time for 45 min;

[0062] (2) Impact strength was tested according to ASTM D256 standard, with specimen size of 63.5*12.7*3.2 mm and notch depth of 2.5 mm;

[0063] (3) Flame retardant properties

[0064] Flammability is evaluated according to the procedures of Underwriter's Laboratory Bulletin 94, entitled "Tests for Flammability of Plastic Materials for Parts in Devices and Appliances" (ISBN 0-7629-0082-2), 5th edition, October 29, 1996, plus all revisions up to and including the revision of December 12, 2003. Several ratings may be applied based on burning rate, extinguishing time, ability to resist dripping, and whether the dripping material burns. According to this procedure, materials can be classified as UL94 HB, V0, V1, V2, 5VA, and / or 5VB;

[0065] (4) The content of siloxane and phosphorus-containing bisphenol monomers was detected by nuclear magnetic resonance spectroscopy;

[0066] Preparatory Examples:

[0067] (1) Preparation of phosphorus-containing bisphenol monomer (DBA-P):

[0068] DOPO (10365 g, 48 mol), o-diallyl bisphenol A (1478 g, containing 9.60 mol of double bond units), ethanol, and 32% sodium hydroxide solution (12 g, 0.096 mol) were added to the reactor, mechanically stirred at 500 rpm, heated to 80°C, and maintained for 4 hours. The solvent was removed by rotary evaporation to obtain a phosphorus-containing bisphenol monomer, named DBA-P.

[0069] (2) Preparation of polyorganosiloxane monomer:

[0070] Octamethylcyclotetrasiloxane (1420g, 4.80mol), tetramethyldisiloxane (40.2g, 0.3mol) and clay catalyst Filtrol 20 (23.4g, 1.6 wt%) were added to a reactor equipped with a stirrer and a thermometer and stirred for 40 minutes to make the material mixture uniform, then the reaction system was heated to 50°C at a rate of 5°C / min and stirred at this temperature for 3 hours, then the temperature of the reaction system was continued to be heated to 120°C at a rate of 5°C / min and stirred vigorously at this temperature for 5 hours, and then the clay catalyst was filtered to remove. Then the material after removing the clay catalyst was placed in a reactor equipped with a stirrer and a thermometer and a mixed solution of 2,4-divinylphenol (149g, 1.02mol) and karstedt platinum catalyst (0.67g) was added dropwise at a rate of 20g / min while stirring, and then stirred at a temperature of 80°C for 13 hours. Subsequently, the unreacted raw materials were distilled off at 200°C under reduced pressure of 0.2 kPa to obtain vinylphenol-terminated polysiloxane with a yield of 99%. The degree of polymerization of PDMS was 55 as determined by nuclear magnetic resonance. For convenience, it is defined as PDMS-55 in this article. Other conditions remained unchanged, and by changing the amount of tetramethyldisiloxane, a monomer with a siloxane degree of polymerization of 89 was prepared (corresponding to an amount of 20.1 g of tetramethyldisiloxane), which is defined as PDMS-89 in this article.

[0071] Further, DOPO (399.5 g 1.85 mol), PDMS-55 (1500 g 0.37 mol), ethanol, 32% sodium hydroxide solution (4.6 g 0.037 mol), mechanically stirred at 500 rpm, heated to 80 ° C, kept reacting for 4 hours, and the solvent was removed by rotary evaporation to obtain a phosphorus-containing polysiloxane monomer, named P-PDMS-55. P-PDMS-89 was prepared by the same preparation method;

[0072] (3) Preparation of phosphorus silicon copolycarbonate:

[0073] The preparation method of P-1 is as follows:

[0074] 7410 g of phosphorus-containing bisphenol, 1000 g of sodium hydroxide, and 7200 g of water were added to a nitrogen-protected mixer, and after 47 g of p-tert-butylphenol was completely dissolved, 12.9 g of catalyst tetrabutylammonium bromide was added to form a sodium phenolate salt water phase;

[0075] In another mixer, add 1139 g of liquid phosgene and 22770 g of dichloromethane (MC), and mix the two evenly; in another mixer, add 640 g of phosphorus-containing polysiloxane monomer (P-PDMS-55) and 2562 g of dichloromethane, and mix the two evenly;

[0076] Subsequently, the sodium phenolate salt water phase is placed in a polymerization reactor, and then the prepared phosgene solution and the prepared comonomer solution are respectively added to the polymerization reactor at a stirring rate of 550 rpm, and at the same time, a 32 wt % sodium hydroxide aqueous solution is added dropwise to the reaction system to keep the pH value of the reaction system at 11.4, and the temperature of the reaction system is maintained at 35°C; after reacting for 2 hours, the reaction system is separated and purified, and the organic solvent is removed to obtain the phosphorus silicon copolycarbonate of the present invention.

[0077] The preparation method of phosphorus silicon copolycarbonate with other compositions is the same as that of P-1 above, except that the feed ratio is changed. The feed ratio is shown in the following table:

[0078] Table 1 Phosphorus Silicon Copolycarbonate Feed Ratio

[0079]

[0080] The test data of the above manufacturing examples are shown in Table 2 below:

[0081] Table 2 Basic physical property test data

[0082]

[0083] The raw materials used in the embodiments and comparative examples are as follows:

[0084] (A) Aromatic polycarbonate:

[0085] PC-1 is a bisphenol A polycarbonate powder with a weight average molecular weight of 22,000 produced by the interfacial phosgene method, produced by Wanhua Chemical Group Co., Ltd.

[0086] PC-2 is a bisphenol A polycarbonate powder with a weight average molecular weight of 28,000 produced by the interfacial phosgene method, produced by Wanhua Chemical Group Co., Ltd.

[0087] PC-3 is a bisphenol A polycarbonate powder with a weight average molecular weight of 34,000 produced by the interfacial phosgene method, produced by Wanhua Chemical Group Co., Ltd.

[0088] (B) Phosphorus Silicon Copolycarbonate

[0089] P-1 to P-6 were prepared in the above preparatory examples;

[0090] P-7: Wanhua Chemical S2060 (MW: 28900 g / mol, PDMS content 20%)

[0091] (C) Additives

[0092] Antioxidant B900 produced by Ciba Specialty Chemicals;

[0093] Lubricant pentaerythritol stearate (PETS), produced by Lonza Corporation, USA;

[0094] Embodiment and comparative example:

[0095] The material preparation process is as follows:

[0096] Whether it is a comparative example or an embodiment, according to the corresponding formula, aromatic polycarbonate, phosphorus silicon copolymer carbonate, antioxidant, and lubricant are put into a high-speed mixer for mixing and stirring, and the mixture is added to a loss-in-weight feeding scale above the feeding port of the screw extruder. The conveying section of the twin-screw extruder is controlled at 210-220°C, the plasticizing section is 225-245°C, and the metering section is 225-240°C. The screw speed is controlled at 200-600rpm, and the vacuum degree of the vacuum device of the twin-screw metering section is controlled to be less than -0.7 bar. The strips are pulled, water-cooled, air-dried, pelletized, and dried to obtain the product.

[0097] Examples 1-10

[0098] The formulations and properties of the polycarbonate compositions of Examples 1-10 are detailed in Table 1.

[0099] Comparative Examples 1-4

[0100] The formulations and properties of the polycarbonate compositions of Comparative Examples 1-4 are detailed in Table 2.

[0101] The polymer P-7 used in Comparative Example 4 was prepared according to Example 3 in Chinese Publication Patent CN112280027 A, with a measured molecular weight of 31000 g / mol and a siloxane content of 25%.

[0102] Table 1 Formulation and properties of the polycarbonate compositions of Examples 1-10

[0103]

[0104]

[0105] Table 2 Formulation and properties of the polycarbonate compositions of Comparative Examples 1-6

[0106]

[0107] By comparing Comparative Examples 1-4 with Example 1, Example 2, Example 6, and Example 10, it is found that the phosphorus-silicon copolycarbonate in the polycarbonate composition of the present invention has excellent compatibility with the polycarbonate material, and the flame retardant properties of the polycarbonate material are greatly improved through the synergistic flame retardant effect of phosphorus-silicon, and the polycarbonate material has halogen-free and environmentally friendly properties. In addition, the phosphorus-silicon copolycarbonate added in the present invention, the polysiloxane chain segment forms a large-sized silicon domain in the material, which can greatly improve the impact resistance of the polycarbonate material.

[0108] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A polycarbonate composition comprising at least the following four components: (1) 65 to 85 parts by weight of an aromatic polycarbonate; (2) 15 to 35 parts by weight of phosphorus-silicon copolycarbonate containing structural units of formula 1 and formula 2, In Formula 2, the p is selected from an integer of 20 to 90, preferably 30 to 50; (3) 0.05 to 1 parts by weight of an antioxidant; (4) 0.1 to 1 parts by weight of a lubricant.

2. The polycarbonate composition according to claim 1, characterized in that The aromatic polycarbonate is a bisphenol A type polycarbonate with a weight average molecular weight of 20,000-40,000, preferably a bisphenol A type polycarbonate with a weight average molecular weight of 22,000-35,000.

3. The polycarbonate composition according to claim 1 or 2, characterized in that The phosphorus silicon copolycarbonate containing structural units of formula 1 and formula 2, the weight fraction of the structural unit shown in formula 1 is 75-95%, preferably 80-90%, and the weight fraction of the structural unit shown in formula 2 is 5-25%, preferably 10-20%; the phosphorus silicon copolycarbonate has a weight average molecular weight of 20000-30000 g / mol; preferably 25000-30000 g / mol.

4. The polycarbonate composition according to any one of claims 1 to 3, characterized in that: The phosphorus-silicon copolycarbonate is obtained by polymerizing the phosphorus-containing bisphenol shown in Formula 3 and the phosphorus-containing polysiloxane monomer shown in Formula 4 with phosgene.

5. The polycarbonate composition according to any one of claims 1 to 4, characterized in that: The antioxidant is any one of hindered phenols, organic phosphorus, thioesters or hindered amines or a mixture of two or more thereof.

6. The polycarbonate composition according to any one of claims 1 to 5, characterized in that: The lubricant is any one of pentaerythritol stearate, modified ethylene bis stearic acid amide and silicone powder or a mixture of two or more thereof.

7. A method for preparing a polycarbonate composition according to any one of claims 1 to 6, comprising: Aromatic polycarbonate, phosphorus silicon copolycarbonate, antioxidant and lubricant are put into a high-speed mixer for mixing and stirring, and then the mixture is put into a twin-screw extruder for extrusion.

8. The preparation method according to claim 7, characterized in that: The temperature of the twin-screw extruder conveying section is 210-220°C, the temperature of the plasticizing section is 225-245°C, the temperature of the metering section is 225-240°C, and the screw speed is 200-600rpm.

Citation Information

Patent Citations

  • Train interior components with low smoke and low heat release and their manufacturing methods

    CN105849171B

  • Efficient intrinsic flame-retardant polycarbonate and preparation method thereof

    CN112898553A

  • Polysiloxane copolymers, thermoplastic composition, and articles formed therefrom

    US20070129492A1

  • Phosphorus-silicon-containing copolymerized polycarbonate, preparation method and composition thereof, and preparation method and application of composition

    CN112280027A

  • Polycarbonate-polysiloxane copolymer, method for producing same, and polycarbonate resin composition containing same

    CN114989407A

Cited By

  • Polycarbonate-based light guide composition as well as preparation method and application thereof

    CN121182170A

  • A polycarbonate-based light-guiding composition, and a method of preparing and using the same

    CN121182170B